2019
DOI: 10.2135/cropsci2018.04.0220
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Communities on Roughs, Fairways, and Putting Greens of Cool‐Season Golf Courses

Abstract: The microbial communities of golf courses provide many ecosystem functions and could be leveraged to provide better N fertility, biocontrol, and thatch degradation. However, little is known about soil bacterial and fungal communities on golf courses or how management affects them. We used metagenomics to identify the soil‐inhabiting bacteria and fungi among three management areas receiving few (roughs), moderate (fairways), and high (putting greens) inputs on three golf courses to determine how management inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
(112 reference statements)
1
10
0
Order By: Relevance
“…In fact, transferring larvae from one soil to another did not alter microbial diversity in the larval gut over the short term, although changes in gut community dispersion potentially reflected a community in transition resulting from exposure to a novel soil community. In general, microbiota in host soils resemble those commonly found in the rhizosphere of turfgrass (Allan-Perkins et al, 2019 ; Azeem et al, 2020 ) and other grass-dominated ecosystems (Bergmann et al, 2011 ; Naylor et al, 2017 ), with soil microbial communities being richer and more diverse compared to the JB gut. Such decreases in microbial richness and diversity between soil and gut have been previously reported in JB (Chouaia et al, 2019 ) and other scarab larvae (Egert et al, 2003 ; Andert et al, 2010 ; Arias-Cordero et al, 2012 ), further supporting the notion that compartment drives variation in community composition to a greater extent than location.…”
Section: Discussionmentioning
confidence: 81%
“…In fact, transferring larvae from one soil to another did not alter microbial diversity in the larval gut over the short term, although changes in gut community dispersion potentially reflected a community in transition resulting from exposure to a novel soil community. In general, microbiota in host soils resemble those commonly found in the rhizosphere of turfgrass (Allan-Perkins et al, 2019 ; Azeem et al, 2020 ) and other grass-dominated ecosystems (Bergmann et al, 2011 ; Naylor et al, 2017 ), with soil microbial communities being richer and more diverse compared to the JB gut. Such decreases in microbial richness and diversity between soil and gut have been previously reported in JB (Chouaia et al, 2019 ) and other scarab larvae (Egert et al, 2003 ; Andert et al, 2010 ; Arias-Cordero et al, 2012 ), further supporting the notion that compartment drives variation in community composition to a greater extent than location.…”
Section: Discussionmentioning
confidence: 81%
“… Note . M1 to M4 refer the metagenomic studies in Table 1: M1, Lê Van et al., 2017; M2, Allan‐Perkins et al., 2019; M3, Doherty, 2018; M4, Zhang et al., 2017; M5, Zhu et al., 2018. ++ indicates species level and + refers to genus level.…”
Section: Resultsmentioning
confidence: 99%
“…The methods in these studies revealed that the main targets for fungal identification were the ITS or the 18S SSU regions, mostly focusing on ITS1 with ITS1/ITS2 primers (White et al., 1990). Sequencing of these regions gave a resolution mostly to the genus level (Allan‐Perkins et al., 2019; Doherty, 2018; Zhang et al., 2017; Zhu et al., 2018), one to the family level (Stacey et al., 2019), and rarely to a species (Lê Van et al., 2017). A summary of the fungal identification sequencing targets, primers, and reference databases of the mentioned studies is presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…These microorganisms are probably involved in the biocontrol, biotransformation and nutrient uptake in plants. Allan-Perkins [162] found that Proteobacteria spp. were the predominant microorganisms in soil samples from a golf course, and they noted that soil management practices significantly influenced fungal abundance, diversity and pathogens.…”
Section: Fungimentioning
confidence: 99%